2018
DOI: 10.1371/journal.pone.0202342
|View full text |Cite
|
Sign up to set email alerts
|

QTL analyses for tolerance to abiotic stresses in a common bean (Phaseolus vulgaris L.) population

Abstract: Common bean productivity is reduced by several abiotic stress factors like drought and low soil fertility, leading to yield losses particularly in low input smallholder farming systems in the tropics.To understand the genetics of stress tolerance, and to improve adaptation of common bean to adverse environments, the BAT 881 x G21212 population of 95 recombinant inbred lines (RILs) was evaluated under different abiotic stress conditions in 15 trials across four locations in Colombia, representing two higher alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 62 publications
6
50
1
1
Order By: Relevance
“…Cultivars considered drought-tolerant can be used as parents to develop improved populations with a high frequency of favorable genes involved in water-deficit tolerance. In addition, the identification of genotypes with contrasting drought tolerance is important in the choice of parents for crosses, to establish segregating populations for future mapping of quantitative trait loci (QTL) [4,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Cultivars considered drought-tolerant can be used as parents to develop improved populations with a high frequency of favorable genes involved in water-deficit tolerance. In addition, the identification of genotypes with contrasting drought tolerance is important in the choice of parents for crosses, to establish segregating populations for future mapping of quantitative trait loci (QTL) [4,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Drought‐resistant genotypes were selected based on deep rooting (BAT 477, SEA 5; Singh et al, 1990; White et al, 1990), high HI under drought (SER 16; Polania et al, 2016b), high shoot vigor under drought (SXB05; Assefa et al, 2013), drought and low‐fertility adaptation (BFS10; Beebe et al, 2008; Suarez‐Salazar et al, 2019), and genotypes described as drought resistant by CIAT due to their high yields under drought conditions (DAB 295, DAB 494; Polania et al, 2016b; Suarez‐Salazar et al, 2019). Drought‐sensitive lines were selected for their commercial use and known sensitivity to drought (Assefa et al, 2013; Polania et al, 2016a, 2017a; Diaz et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers at the International Center for Tropical Agriculture (CIAT) select and develop drought‐resistant common bean varieties, with much of the selection having integrated grain yield and several morphophysiological traits such as pod harvest index (PHI), g s , deep rooting, and high vigor under drought (Beebe et al, 2013; Rao, 2014; Polania et al, 2016a, 2016b). Selected drought‐resistant germplasm was crossed with germplasm containing additional positive traits including seed composition and disease resistance, to develop improved cultivars and recombinant inbred line populations for genetic studies (Polania et al, 2016a; Diaz et al, 2018). However, the genotypic variation of Δ 13 C and its relationship to yield under conditions differing in water availability have not been studied in the parental lines of these CIAT mapping populations.…”
mentioning
confidence: 99%
“…For example, Diaz et al. (2018) identified two QTLs related to maturity on chromosome 1 and 8, and a yield QTL on chromosome 4 in common bean under drought stress. Dramadri et al (2019) identified 18 QTLs for phenology, yield components and partitioning traits (i.e., pod harvest index and pod partitioning index) on chromosomes 1, 2, 3, 4, 6 and 11 under drought stress and non‐stress conditions in Andean common bean gene pool.…”
Section: Quantitative Trait Loci (Qtls) Affecting Agronomic Physiolomentioning
confidence: 99%